Miscellanies : embracing nature, addresses, and lectures / by R.W. Emerson. - Emerson, Ralph Waldo, 1803-1882. (Tufts University. Tisch Library., 2016)
New and revised edition.; 1 online resource (vi, 383 pages); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.